Programmed cell death protein‐1 (PD‐1)‐targeted immunotherapy in advanced hepatocellular carcinoma: efficacy and safety data from an international multicentre real‐world cohort - Scheiner, Bernhard; Kirstein, Martha M.; Hucke, Florian; Finkelmeier, Fabian; Schulze, Kornelius; von Felden, Johann; Koch, Sandra; Schwabl, Philipp; Hinrichs, Jan B.; Waneck, Fredrik; Waidmann, Oliver; Reiberger, Thomas; et al. (Alimentary pharmacology & therapeutics, 2019)
Summary Background Programmed cell death protein‐1‐targeted immunotherapy has shown promising results in phase II studies of hepatocellular carcinoma. Aim To evaluate safety and efficacy of nivolumab and pembrolizumab in an international, multicentre, real‐world cohort of patients with advanced hepatocellular carcinoma. Methods Sixty‐five patients treated with nivolumab (n = 34) or pembrolizumab (n = 31) between July 10, 2015 and December 31, 2018 (data cut‐off) across six centres in Austria and Germany were retrospectively analysed. Results Child‐Pugh class A/B/C was 32 (49%)/28 (43%)/5 (8%). Immunotherapy was used as systemic first‐/second‐/third‐/fourth‐line treatment in 9 (14%)/27 (42%)/26 (40%)/3 (5%) patients. Fifty‐four patients had at least one follow‐up imaging and were, therefore, available for radiological response assessment. The overall response and disease control rates were 12% and 49% respectively. Of 52 evaluable patients, four (8%) had hyperprogressive disease. Median time to progression was 5.5 (95% CI, 3.5‐7.4) months, median progression‐free survival was 4.6 (95% CI, 3.0‐6.2) months, and median overall survival was 11.0 (95% CI, 8.2‐13.8) months. Most common adverse events were infections (n = 7), rash (n = 6), pruritus (n = 3), fatigue (n = 3), diarrhoea (n = 3) and hepatitis (n = 3). Efficacy and safety results were comparable between Child‐Pugh A and B patients; however, median overall survival (OS) was shorter in Child‐Pugh B patients (16.7 vs 8.6 months; P = 0.065). There was no difference in terms of efficacy and adverse events between patients who received immunotherapy as first‐/second‐line and third‐/fourth‐line respectively. Conclusions Programmed cell death protein‐1‐targeted immunotherapy with nivolumab or pembrolizumab showed promising efficacy and safety in patients with advanced hepatocellular carcinoma, including subjects with Child‐Pugh stage B and patients with intensive pretreatment.